Why do boys and girls perform differently on PISA Reading in Finland? The effects of reading fluency, achievement behaviour, leisure reading and homework activity - Torppa M; Eklund K; Sulkunen S; Niemi P; Ahonen T (WILEY, 2022)
The present study examined gender gap in Program for International Student Assessment (PISA) Reading and mediators of the gender gap in a Finnish sample (n=1,309). We examined whether the gender gap in PISA Reading performance can be understood via the effects of reading fluency, achievement behaviour (mastery orientation and task-avoidant behaviour) or the amount of time spent with leisure reading and homework. Girls outperformed boys in all measures except for achievement behaviour. The models explaining PISA Reading were not different: For boys and girls, reading fluency, mastery orientation, leisure book reading and homework explained the variance in PISA Reading scores. The gender effect on PISA Reading was, however, for the most part mediated by differences in reading fluency. These findings suggest that while mastery orientation, homework activity and leisure book reading are concurrent predictors of PISA Reading over and above reading fluency, they do not explain gender difference.